Study on the relationship between fuel fragmentation during a LOCA and pellet microstructure. Issue 12 (2nd December 2021) - Yamauchi, Akihiro
ABSTRACT: To systematically examine the relationship between the fuel fragmentation during a loss-of-coolant accident (LOCA) and the pellet microstructure, heating tests were conducted on micro fuel samples obtained from various radial positions of high-burnup fuel. The extent of the fuel fragmentation was evaluated via fission gas release rate and post-test microscopies. The results provide direct evidence for the contribution of the high-burnup structure (HBS) on the fine fuel fragmentation during a LOCA. The paper also demonstrates that the samples with a local burnup of lower than 72 GWd/tU did not fragment severely, which is in good agreement with the previously proposed burnup threshold. Heating tests incorporating stepwise depressurization from high pressure were also conducted to examine the evolution of fission gas release throughout the depressurization. The suppressing effect of hydrostatic pressure on fuel fragmentation is further confirmed. Additionally, the paper also provides results that suggest that most of the fine fragmentation at the HBS occurs during depressurization from 20 to 2 MPa.